Cyclic behavior of welded elliptical-shaped RWS moment frame. (December 2020) - Davarpanah, Mohammad; Ronagh, Hamid; Memarzadeh, Parham; Behnamfar, Farhad
Abstract: One of the disadvantages of the reduced beam section (RBS) connection is the possibility of lateral-torsional buckling in the beam. Based on previous researches, reducing the cross-section along the web rather than the flange is one of the effective ways to prevent this phenomenon. The authors, in some part of their study on reduced web section (RWS) connections reported in references, have proposed new details about RWS connections by creating an elliptical opening in the beam web and presented recommendations for optimum ranges of the geometrical parameters. The main aim of this paper is to investigate the cyclic performance of an eight-story three-bay welded moment frame having elliptical-shaped RWS ( E -RWS) and to compare it with that of the frames having the conventional full- or reduced-beam sections. For this purpose, at first, two connections with the E -RWS and with the common radial-cut (R-RBS) were experimentally tested under the cyclic loading and their performances were examined. The results showed the priority of the E -RWS over the R-RBS in terms of strength, stiffness, ductility, and lateral-torsional stability. Following that, a step-by-step design process for the E -RWS connection was presented. At last, by using an FEM analysis verified by the experimental data, the cyclic performance of an E -RWS frame was compared with that of the full- and RBS frames. According to the results of this study, the creation of an elliptic opening in the beam web can replace the reduced-beam section connections as a suitable method, which can improve the seismic behaviors of MRFs.